The consistency between prescriptive and deliberative accountants? Moral reasoning: case in Yemen - Al-Aidaros, Al-Hasan; Abdul Ghani, Abdullah; Md. Idris, Kamil (IRMBR, 2014)
Over the years, and based on Western studies, researchers concluded that the level of accountants’ moral reasoning is low, i.e. pre-conventional moral reasoning, which mean professional accountants do not have a higher level of moral reasoning than average individuals do and other professionals.However, such level may probably not be true to Muslim’s accountants because they are operating in an Islamic environment that can shape the way they behave. To identify the level of accountants’ moral reasoning, this study used Defining Issues Test specifically for accounting (DIT-A) and from an Islamic perspective.It is important to measure how Yemeni professional accountants perceive prescriptively (ideally) and deliberatively (realities) on issues related to the moral code of conduct.This is because Islam emphasizes consistency between thought and action. Therefore, the purpose of this paper is to examine the link between prescriptive and deliberative accountants’ moral reasoning.Data were collected from 138 professional accountants in four main cities of Yemen i.e. Sana’a, Hadhramout, Taiz, and Aden. Results showed that Yemeni professional accountants exhibit higher level of moral reasoning beyond the conventional level and there is a consistency between the prescriptive and deliberative moral reasoning. Besides, the limitations of the study are highlighted